E-report for FSKM faulty facilities / Zanariah Abdul Wahab - Abdul Wahab, Zanariah (2010)
This system name is E-Report for FSKM Faulty Facilities. The purpose is to develop complaint of faulty facilities for FSKM in order to meet their need in managing their facilities in FSKM. This system will be used by FSKM staffs, students and the administrator. The system architecture that used to design and develop this system is WAMP Server which is combination of Microsoft Windows, Apache, MySQL and PHP. I hope this system will enhance in arrange complaint by student or staff.